Korelasi Citra Merek, Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Pupuk Pada PT Surya Mentari Saktindo Gresik - Rosyadan, Mohammad Da’i; Sukaris, Sukaris (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2024)
The ability to differentiate products is becoming an increasingly important factor in attracting consumers. In order to remain competitive, conventional marketing strategies must be enhanced, and the potential of digitalisation in the marketing sector should not be overlooked. In the context of relentless competition, it is imperative for companies to pursue continuous improvement without becoming overly complacent about achieving their goals. The role of product brand image, product quality and pricing has an impact on the growth of PT Surya Mentari Saktindo Gresik fertilizer company, especially in light of the continued promotion of the optimization of marketing through social media as a means of achieving marketing goals. The quantitative research method was selected for this study to enable the effect of the independent variable on the dependent variable to be accurately described. The results demonstrate that variable X2 has no positive effect on variable Y, whereas variables X1 and X2 have a significant effect. It can be concluded that the consumer's decision to purchase fertiliser products is based on the impact of brand image and product reliability.